Implementasi Program Keluarga Harapan (PKH) di Provinsi Jawa Tengah - Sofianto, Arif (Puslitbangkesos Kementerian Sosial RI, 2020)
The Family Hope Program (PKH) is a conditional social assistance program for very poor families aimed at improving the quality of life and well-being. PKH is considered to provide direct benefits to help with education and health costs, but it has not yet affected social economic status. PKH implementation is considered not on target, giving rise to potential conflicts, and other technical problems. Central Java Province is the region that has the second highest poverty rate in Indonesia, and a very large number of PKH recipients. This study aims to: 1) Describe the implementation of PKH in Central Java; 2) Analyze community attitudes towards the implementation of PKH in Central Java; 3) Formulating the concept of PKH renewal desired by the community. This study used mixed method approach (qualitative and quantitative). This reseacrh conducted in 15 districts with the highest poverty rate in Central Java. Informants involved in this study were the recipient of the handler, PKH assistant, village officials, and local government officials. Data collection instruments are questionnaires, FGDs, and interview guides. Data analysis with an interactive model developed by Miles and Huberman, which includes data reduction, data display, and data verification. The conclusions of this study are: 1) The implementation of PKH in Central Java in terms of procedures and managerial aspects is considered good, but the program targets are not appropriate because of invalid data, amounting to 21.54 percent of PKH recipients are not poor, and only 13.99 percent of PKH recipients are poor and 26,21 percent very poor. 2) The community feels the benefits of PKH to ease their living expenses and if possible increase the amount, on the other hand there are still many poor families who have not received assistance to cause conflict and suspicion. 3) The renewal of PKH needed is to have a dimension of sustainability, involving the community in program planning, as well as educating the poor to be empowered and productive. The recommendations of this study are: 1) updating data integrated with population data, as well as collaboration between village, district/city, and provincial governments; 2) education for the community to escape poverty and submit correct data. 3) increasing training activities, increasing competitiveness and productivity. 4) local governments contribute to the addition quota of PKH recipients and companion staff.Â Keywords: PKH, Poverty, Central Java